2020
DOI: 10.18632/aging.103304
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation end products mediate damage and apoptosis of periodontal ligament stem cells induced by the JNK-mitochondrial pathway

Abstract: Background: Recent studies have confirmed the bidirectional relationship between the two and the exacerbation of periodontitis by type II diabetes mellitus (T2DM), the pathogenic mechanism has not yet been clarified, AGEs has been linked to the pathogenesis of both periodontitis and T2DM, JNK signaling pathway might play a important role to explain the inner mechanism. Objectives: To study advanced glycation end products (AGEs) activate the innate immune system of the host by activating oxidative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Disruption of ALP can also lead to cell death by nonspecific degradation of cellular components or through the activation of apoptosis, the programmed cell death that stimulates proteases to degrade all the necessary cellular components. Apoptosis has an extrinsic pathway that activates caspase-8 through death receptors such as FasL and TNF-α receptors (TNFR), while the intrinsic pathway with a loss of mitochondrial membrane integrity and subsequent release of cytochrome c [15,101] activates caspase-9 to release Bcl-2 family members (Bax and Bak) and stimulate the JNK signaling pathway [15,101]. Caspases-3 and -8 levels were reduced in T2DM-periodontitis patients, while caspase-9 showed the same trend as that in healthy subjects [15].…”
Section: Cellular Debris Eliminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of ALP can also lead to cell death by nonspecific degradation of cellular components or through the activation of apoptosis, the programmed cell death that stimulates proteases to degrade all the necessary cellular components. Apoptosis has an extrinsic pathway that activates caspase-8 through death receptors such as FasL and TNF-α receptors (TNFR), while the intrinsic pathway with a loss of mitochondrial membrane integrity and subsequent release of cytochrome c [15,101] activates caspase-9 to release Bcl-2 family members (Bax and Bak) and stimulate the JNK signaling pathway [15,101]. Caspases-3 and -8 levels were reduced in T2DM-periodontitis patients, while caspase-9 showed the same trend as that in healthy subjects [15].…”
Section: Cellular Debris Eliminationmentioning
confidence: 99%
“…PDL fibroblasts undergo apoptosis, which causes a decrease of almost 40% in its density in rats with DM and periodontitis, when compared to normoglycemic rats after periodontitis induction [103]. Furthermore, periodontal ligament cells also suffer apoptosis mediated by a complex interaction between the JNK signaling pathway and mitochondria under high levels of TNF-α, AGE, and endogenous ROS [101,102]. In contrast, a burst in bone formation with increased osteoblast cells and amounts of osteoid in non-DM subjects was observed after removal of periodontitis ligature [103,104].…”
Section: Cellular Debris Eliminationmentioning
confidence: 99%
“…O 2 − in mitochondria can increase the production of intracellular advanced glycation end products (AGEs) in cells [67,68]. AGEs can add oxygen radical, and the activation of AGEs receptor can cause intracellular oxidative stress, which in turn causes inflammation in endothelial cells [69][70][71]. Therefore, AGEs eventually lead to atherosclerosis by modifying the extracellular matrix and circulating lipoproteins and activating AGEs receptors [66] 3 Oxidative Medicine and Cellular Longevity vascular calcification through the pathway of hypoxia-inducer/pyruvate dehydrogenase kinase 4 [72].…”
Section: Atherosclerosismentioning
confidence: 99%
“…Phosphorylation of JNKs and p38 causes upregulation of proapoptotic transcription factors in the nucleus, leading to an increase in apoptosis [82,83]. In EPCs [41,42,46] and MSCs [53,54,58,60], JNK/MAPK pathways are also activated by AGEs, leading to an increase in apoptosis. In addition, AGEs activate the MAPK pathways via excessive ROS generation.…”
Section: Rage Activation Leads To Map Kinase Activation Andmentioning
confidence: 99%
“…Mesenchymal Stem Cells.Nine articles have studied the effect of AGEs on mesenchymal stem cells (MSCs, Table3) derived from BM, tendons, periodontal ligament, or the pancreas. Despite differences in the concentration(25 up to 800 μg/ml) and duration (6 hours up to 19 days) of AGEs exposure, a decrease in proliferation associated or not with an increase in apoptosis, was observed in 7 out of 9 studies[53][54][55][56][57][58][59][60]. In contrast, Sakamoto et al[56] observed a trend of decreased proliferation of MSCs by AGEs, but results did not reach significance.…”
mentioning
confidence: 95%